2022
DOI: 10.3390/biomedicines10010196
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking Na+/Taurocholate Cotransporting Polypeptide (NTCP) as a Drug Target for HBV Infection: From Protein Engineering to Drug Discovery

Abstract: Hepatitis B virus (HBV) infections are among the major public health concerns worldwide with more than 250 million of chronically ill individuals. Many of them are additionally infected with the Hepatitis D virus, a satellite virus to HBV. Chronic infection frequently leads to serious liver diseases including cirrhosis and hepatocellular carcinoma, the most common type of liver cancer. Although current antiviral therapies can control HBV replication and slow down disease progress, there is an unmet medical nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 95 publications
0
19
0
Order By: Relevance
“…Although, during revision of the manuscript, three independent cryo-EM structures of human NTCP were published [13][14][15], partly with bound viral myr-preS1 peptide, the precise molecular interactions between the host-derived NTCP receptor and the HBV surface proteins are still not fully understood. Experimental approaches, such as protein engineering and computational biology methods, are powerful tools in exploring motifs within the NTCP protein that are essential for regulation of its HBV affinity during infection [3,9,10,12,23,24,32,33]. In this study, we identified a novel NTCP tyrosine-enriched motif 139YIYSRGIY146 that is significantly involved in the regulation of NTCP-HBV preS1 interactions and, thus, in the control of NTCP receptor function (Figure 7A,B).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Although, during revision of the manuscript, three independent cryo-EM structures of human NTCP were published [13][14][15], partly with bound viral myr-preS1 peptide, the precise molecular interactions between the host-derived NTCP receptor and the HBV surface proteins are still not fully understood. Experimental approaches, such as protein engineering and computational biology methods, are powerful tools in exploring motifs within the NTCP protein that are essential for regulation of its HBV affinity during infection [3,9,10,12,23,24,32,33]. In this study, we identified a novel NTCP tyrosine-enriched motif 139YIYSRGIY146 that is significantly involved in the regulation of NTCP-HBV preS1 interactions and, thus, in the control of NTCP receptor function (Figure 7A,B).…”
Section: Discussionmentioning
confidence: 90%
“…To date, little is known about the mechanistic insights into the process of initial NTCP-HBV complex assembly and NTCP-mediated virus entry into hepatocytes [9,10]. Although, during revision of the manuscript, three independent cryo-EM structures of human NTCP were published [13][14][15], partly with bound viral myr-preS1 peptide, the precise molecular interactions between the host-derived NTCP receptor and the HBV surface proteins are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations